2001
DOI: 10.4102/jsava.v72i4.656
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frog pressure and downward vertical load on hoof wall weight-bearing and third phalanx displacement in the horse - an in vitro study : research communication

Abstract: A shoe was designed to combine the advantages of a reverse shoe and an adjustable heart bar shoe in the treatment of chronic laminitis. This reverse even frog pressure (REFP) shoe applies pressure uniformly over a large area of the frog solar surface. Pressure is applied vertically upward parallel to the solar surface of the frog and can be increased or decreased as required. Five clinically healthy horses were humanely euthanased and their dismem-bered forelimbs used in an in vitro study. Frog pressure was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Considerable information on the anatomical and force constraints of the distal limb has been generated through in vitro and in vivo studies on various aspects of the hoof complex, which is both rigid and flexible to support and accommodate the interaction of the hoof with the surface (Back 2001;Hinterhofer et al 2001;Roepstorff et al 2001;Olivier et al 2001;Thomason et al 2001Thomason et al , 2005. Movement of the hoof capsule during movement has been quantified by the use of strain gauges, motion analysis systems and potentiometers (Dejardin et al 1999(Dejardin et al , 2001Roepstorff et al 2001;Thomason et al 2002).…”
Section: Distal Limb Loading During the Support Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Considerable information on the anatomical and force constraints of the distal limb has been generated through in vitro and in vivo studies on various aspects of the hoof complex, which is both rigid and flexible to support and accommodate the interaction of the hoof with the surface (Back 2001;Hinterhofer et al 2001;Roepstorff et al 2001;Olivier et al 2001;Thomason et al 2001Thomason et al , 2005. Movement of the hoof capsule during movement has been quantified by the use of strain gauges, motion analysis systems and potentiometers (Dejardin et al 1999(Dejardin et al , 2001Roepstorff et al 2001;Thomason et al 2002).…”
Section: Distal Limb Loading During the Support Phasementioning
confidence: 99%
“…The hoof deforms continually throughout loading during the stance phase. During the initial loading phase the distal phalanx pulls the dorsal hoof wall backwards and downwards, pushes the quarters outward, causing the bulbs of the heels to expand (Olivier et al 2001;Roepstorff et al 2001;Thomason et al 2002). Shoeing limits this deformation and decreases bulb expansion (Hinterhofer et al 2001;Roepstorff et al 2001).…”
Section: Distal Limb Loading During the Support Phasementioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the myriad of homemade and commercially available products with varying degrees of evidence that weight bearing is altered. 5,[8][9][10][11][12][13] Foam supports have been advocated by many practicing veterinarians and farriers, but scientific evidence for their use has previously been unavailable. 3,4,14,15 The present study revealed that total contact surface area was significantly increased up to 48 hours after placement of foam sole supports.…”
Section: Discussionmentioning
confidence: 99%
“…The palmar/plantar part of the feet is filled using a filler paste with a higher shore value to support the not painful and still well perfused frog. 86…”
Section: Box 2 Principles Of Management Of Laminitis In the Geriatric...mentioning
confidence: 99%